Identifikasi Upaya Guru Dalam Membangkitkan Minat Belajar Siswa Pada Pembelajaran Biologi di Kelas XI MIPA SMA Negeri Sekecamatan Dondo - Nadia; Gamar Binti Non Shamdas; Amalia Buntu; Mohammad Jamhari; Bustamin; Vita Indri Febriani (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to identify teachers' efforts in arousing students' interest in biology learning in public high schools in Dondo District. The study used a descriptive qualitative approach with research instruments in the form of observation sheets, questionnaires, and interview guidelines. Data collection techniques were carried out through observation, questionnaires, and interviews. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions, while the questionnaires were processed descriptively to identify trends in each indicator of teacher efforts. The results showed that teachers had made various efforts to arouse students' interest in learning, with the highest achievement in the indicator of creating a pleasant atmosphere, followed by giving praise and varied learning methods, and efforts to relate the material to everyday life. Meanwhile, the indicator with the lowest achievement was providing feedback that had not been given specifically to each student. This finding was reinforced by the results of interviews that showed that teachers tried to create interesting learning through a variety of methods, concrete examples, and positive interactions during learning. This study concludes that teachers' efforts to arouse students' interest in learning biology have been effective, but the provision of feedback and strengthening of more equitable learning collaboration needs to be improved.